Extensive Reading Strategy and Reading Comprehension: Individual vs Group Instruction - Sarah V. Tomatala; Jonathan H. Tobing; Caroline Victorine Katemba (LPPM Universitas Advent Indonesia, 2024)
Reading in a foreign language (English) has been a problem for primary school kids in remote places in Indonesia. The purpose of this study is to determine if there is a significant difference in the effect of extensive reading (ER) between individual and group teaching. Students were divided into two categories, one class read individually, and the other class read in groups. This is a quantitative study. The pre-test and post-test research design was employed in this study. A comprehension test was given to the participants before and after the reading activities. The results of this study demonstrate that participants in both groups have improved their reading comprehension scores. Additionally, there is a noticeable difference between students who received ER instruction individually and those who received ER instruction in a group; both groups improved in their reading scores, as can be clearly seen from the post-test score as well as from the computed gain score of the ER group, which attained a higher score. The post test of the ER-individual is 51.39, and the normalized gain is 0.31, while the post test of the ER-group is 70.30, and its normalized gain is 0.38. Therefore, there was a significant difference between individual and group teaching. This study also revealed that the approach used to enhance pupils' reading comprehension received favorable feedback. Therefore, it is recommended to use ER groups for reading comprehension, especially for primary pupils.